Developing Proteus video tutorials as interactive mathematics learning media based on a realistic approach - Nurul Asma; Rizka Sylvia (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
The advantages of video tutorials as an alternative learning media in mathematics are significant. Video tutorials are easily used because they are not limited by space and time constraints. For teachers who lack competency in using technology, such learning media greatly assist the teaching process in achieving the desired outcomes. Proteus video tutorials specifically explain the application of Proteus software. These videos are designed based on a realistic approach, where learning begins with real-world contextual problems. The purpose of this study is to develop interactive mathematics learning media through realistic approach-based Proteus video tutorials that are valid and practical. The research method employed is Research and Development (R&D), adapting the ADDIE development model. This model comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The research results indicate that the video is considered valid, obtaining a validation score of 93%, which falls into the very valid category, and practical, with a score of 94%, indicating a very practical category. Furthermore, the video is developed with the characteristics of a realistic approach.